RESTRICTING IMMIGRANTS, COLONIAL INHERITANCE AND POLITICAL INTERESTS: AUSTRALIA’S CITIZENSHIP TEST UNDER THE HOWARD GOVERNMENT - Asep Iqbal (JISPO : Jurnal Ilmu Sosial dan Ilmu Politik, 2018)
In 2006, Australia under the Howard government proposed a citizenship test aimed at restricting immigration and toughening citizenship requirements. To understand this proposed citizenship, this essay attempts to analyze the basic ideas of the test by explaining its possible relationship with Australia’s past history and Australia’s dependence on the ‘superpower’ countries in the issue. It explains that the proposed citizenship test reflected John Howard’s political brands and manifested his wonderful skills in understanding and exploiting the living fears of ‘the other’ among Australian people for political gain in his second term. The huge support for the proposed citizenship test indicated that the fear of ‘the other’ and ‘potential enemies’ was still evident among Australian. It also served as evidence that multiculturalism was under threat because people considered it as a policy that undermines dominant culture.  The article argues that Australia’s colonial past still plays a role in people’s attitudes and government policies. “The chains of colonial inheritance” has not disappeared in contemporary Australia.